Uji Adaptasi dan Stabilitas Hasil Enam Genotipe Cabai Hibrida di Dataran Tinggi Jawa Barat (Adaptation and Yield Stability of Six Hybrid Chili Genotypes in Highland Area of West Java) - nFN Kusmana; Rinda Kirana; Astiti Rahayu (Indonesian Center for Horticulture Research and Development, 2019)
Uji adaptasi dilakukan untuk mengestimasi interaksi antara Genotipe dengan Lingkungan, sehingga dapat ditentukan apakah genotipe yang diuji adaptif pada lingkungan yang spesifik atau stabil pada lingkungan yang luas. Tujuan pengujian ialah mendapatkan informasi tentang stabilitas hasil cabai hibrida yang ditanam pada tiga lokasi di Jawa Barat. Pengujian ditata dengan menggunakan Rancangan Kelompok Lengkap Teracak pada tiga lokasi pengujian yaitu di Kab. Bandung, Kab. Bandung Barat dan Kab. Garut. Populasi tanaman untuk tiap-tiap plot penelitian ialah 30 tanaman dengan empat ulangan. Hasil analisis ragam gabungan terlihat bahwa nilai kuadrat tengah genotipe lebih tinggi dari nilai kwadrat tengah interaksi genotipe x lingkungan hal ini memberikan indikasi bahwa pengaruh genetik lebih dominan dibandingkan faktor lingkungan. Varietas (genotipe) yang diuji berbeda sangat nyata sehingga menunjukkan adanya perbedaan potensi hasil diantara varietas dan terjadi interaksi antara genotipe dengan lingkungan. Genotipe stabil berdasarkan perhitungan MSTATC ialah H-1 dan Cosmos. Genotipe Batalion dan Merona tidak stabil karena nilai T hitung lebih besar dari T tabel sementara Genotipe H 2 dan Hot Beauty tidak stabil karena hasil dibawah rerata. Implikasi dari penelitian ialah didapatkan informasi genotipe cabai yang stabil pada agroekosistem dataran tinggi Jawa Barat. KeywordsGenotipe cabai hibrida (Capsicum annuum); Adaptasi; Stabilitas; Jawa BaratAbstractAn adaptation test was carried out to estimate the interaction between genotypes and the environment, to be able to determine whether the genotypes tested were adaptable in a specific or stable in a wide range of environments. The objective of this study were to obtain the stability level of the hybrid chili tested at three highland West Java locations. The study was arranged using a randomized complete block design with four replications. The treatment consisted of six hybrid chili genotypes tested at three test locations, i.e. West Bandung District, Bandung District, and Garut District. The experimental unit was a plot containing 30 plants. Results showed that the combined analysis of variance (ANOVA) showed that the mean square of the genotype was higher than that of genotype x environment interaction, indicating that the genetic effect was more dominant than that of environmental factors. Genotypes tested were highly significant (p < 0.01) indicating difference yield potential among the genotypes tested. There was a significant interaction between the genotype with that of the environment. The stable genotypes determined based on MSTATC analysis obtained two stable genotypes, i.e. H-1 and Cosmos. Genotypes Batalion and Merona, on the other hand were not stable because the T value counted was greater than that of T table. The genotypes H-2 and Hot Beauty were also found not stable because of low yield performances. The implication of this research was that the stable hybrid chili genotypes obtained from this study can be recommended to be registered as candidates as chili paper new varieties.